The survey of impact of entrepreneurial courses on intention and psychological characteristics of physical education students (a case study of Iranian universities) - Fahimeh Rezaeı; Ali Zareı; Faride Ashraf Ganjoueı (Türk Spor ve Egzersiz Dergisi)
Recently, according to increasing growth of young population and limitations of employment opportunities, empowering youth and their guidance toward entrepreneurship has been the most important country authorities’ programs. In spite of detection of the importance of sport in the knowledge economy and entrepreneurship and efforts by universities in the country and the Ministry of Sport and Youth in order to teach entrepreneurship, effect of entrepreneurship education in physical education students and higher education institutions has not been studied. Therefore, the primary purpose of this paper is to study and evaluate effect of entrepreneurship education in schools of physical education in the Iran. Thus, one of the most important actions, in order make entrepreneurial behavior in them, is to form entrepreneurial intend and attitude in them. The research method is descriptive and applied one. Statistical population of this study includes all physical education colleges affiliated to the Ministry of Science, Research and Technology. Target population includes all students existed in schools as well as individuals who were registered. A validity questionnaire having the stability α=0/91 was used in order to collect data. Data analysis was performed in two levels by using spss18 software. Results show that entrepreneurship intention of participants in entrepreneurship classes is different than students who do not participate in entrepreneurship classes. In fact, students participated in entrepreneurship classes are more inclined to entrepreneurship. Among contents and popular headlines to train entrepreneurship, the issues such as marketing, principles of launching business, innovation, entrepreneurial characteristics and definitions and concepts of entrepreneurship were presented for students in classes. This study presented basis for accepting additional research on sport-entrepreneurship education. Also, it provides valuable perspectives for universities and other sectors in order to determine the basic characteristics of effective teaching methods in the field of Sport Entrepreneurship that is along with national entrepreneurship development action plan.